(untitled) (American Journal of Innovation in Science and Engineering, 2023)
Natural polysaccharides are being explored as the matrices for attaining speciality materials for pharmaceutical, medicinal and environmental applications via chemical modification such as grafting. Psyllium polysaccharide-based hydrogels and nanogels have potential biomedical and water purification applications due to their advantageous properties such as stimulus responsiveness, biocompatibility, target drug delivery and stability. The present study aims to synthesise hydrogel and nanogels of psyllium and attain comparative data for the two to undermine their potential applications. Psyllium– cl –N,N–MBAm–poly(AAm) hydrogel (Psy-MBAm-AAm – hg) and Psyllium– cl –N,N–MBAm–poly(AAm) nanogel (Psy-MBAm-AAm – ng) were synthesised by grafting acrylamide (AAm) onto psyllium using ammonium persulphate (APS) as a free radical initiator in a redox system where N, N-methylene bisacrylamide acted as a crosslinker. The comparative study of synthesised gels was carried out by studying swelling characteristics at acidic and basic pH (7 and 4) and at varied temperatures for both matrices. The synthesised hydrogel and nanogels were subjected to characterisation by Fourier transform infrared spectroscopy (FTIR), Field Emission Scanning Electron Microscopy (FESEM), and Zeta Potential Analysis to get evidence for successful synthesis and nanogel formation.